2015
DOI: 10.1088/0960-1317/25/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Microfeature edge quality enhancement in excimer laser micromachining of metal films by coating with a sacrificial polymer layer

Abstract: A novel technique for enhanced excimer laser micromachining of metallic thin films by first coating the metal film with a thin polymer film is presented. The sacrificial polymer film acts as a protective and a clamping layer, preventing the metal film from undergoing cracking and damage during the laser ablation. The machined patterns are characterized regarding their quality in terms of edge roughness, lateral overcut and boundary integrity in proximity machining. Significant improvement in these aspects is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is because the 1 lm thick polymer layer gets ablated within a few nanoseconds of the beginning of the pulse [12]. This is because the 1 lm thick polymer layer gets ablated within a few nanoseconds of the beginning of the pulse [12].…”
Section: Aluminum Film Machining (Without and With Polymer Coating)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the 1 lm thick polymer layer gets ablated within a few nanoseconds of the beginning of the pulse [12]. This is because the 1 lm thick polymer layer gets ablated within a few nanoseconds of the beginning of the pulse [12].…”
Section: Aluminum Film Machining (Without and With Polymer Coating)mentioning
confidence: 99%
“…Chromium films [chromium being a refractory metal [12]], undergo cracking during irradiation with excimer lasers [18]. Cracking occurs irrespective of the film getting ablated or not.…”
Section: Chromium Film Machining (Without and With Polymer Coating)mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, in the literature, studies had been carried out to understand the effect of the spot overlap on the machined channel roughness at an oblique angle and concluded that roughness decreases with the increase in the overlap. 25 However, in the literature, the researchers had not discussed the effect of varying spot overlap on the machining time “T m .” Given that machining time is an essential factor in an industrial environment where a high production rate is required along with superlative quality of the product, a study for optimum spot overlap is required. Furthermore, the effect of mask shape on machining roughness and machining time has not been discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%